nifH gene expression and diversity in geothermal springs of Tengchong, China - Song, Zhao-Qi; Wang, Li; Liang, Feng; Zhou, Qingfeng; Pei, Dongli; Jiang, Hongchen; Li, Wen-Jun (Frontiers in Microbiology, 2022)
Terrestrial hot springs have been suggested to harbor diverse diazotrophic lineages by using DNA-based nifH gene phylogenetic analysis. However, only a small amount of diazotrophs were ever confirmed to perform nitrogen fixation. In order to explore the compositions of active diazotrophic populations in hot springs, the in situ expression and diversity of nifH and 16S rRNA genes were investigated in the sediments of hot springs (pH 4.3-9.1; temperature 34-84 ºC) in Tengchong, China, by using high-throughput sequencing. The results showed that active diazotrophs were diverse in the studied Tengchong hot springs. The main active diazotrophs in high-temperature hot springs were affiliated with Aquificae, while those in low-temperature hot springs belonged to Cyanobacteria and Nitrospirae. Such dominance of Aquificae and Nitrospirae of diazotrophs has not been reported in other ecosystems. This suggests that hot springs may harbor unique active diazotrophs in comparison with other type of ecosystems. Furthermore, there were significant differences in the phylogenetic lineages of diazotrophs between hot springs of Tengchong and other regions, indicating that diazotrophs have geographical distribution patterns. Statistical analysis suggests that the expression and distribution of nifH gene were influenced by temperature and concentrations of ammonia and sulfur seem in Tengchong hot springs. These findings avail us to understand element cycling mediated by diazotrophs in hot spring ecosystems.